Pelatihan Pembuatan Modul Dan Workbook Printable Bertemakan Kreatifitas Bagi Tutor Di Lembaga Kursus SAS ANA Medan - Hasibuan, Ahmad Laut; Wariyati, Wariyati; Harahap, Rosmawati; Barus, Efendi; Dara, Ferbri Risma; Sanjaya, Ferry (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the non-formal education institutions in Medan is the SAS ANA Group course institution, which employs 12 tutors. These tutors come from non-education degree backgrounds, and some are still university students. The aim of this Community Service Program (PKM) is to provide tutors at the SAS ANA Group with experience in creating printable modules and workbooks with a creativity-based theme. The implementation method used is PAR (Participatory Action Research), which is interpreted as a participatory approach involving group members—in this case, tutors at SAS ANA Group in Medan—carried out with high enthusiasm to achieve the goal of creating creativity-themed printable modules and workbooks.The results of the program show that (a) tutors at SAS ANA were enthusiastic during the training sessions, (b) tutors expressed a strong interest in learning more about e-modules and printable workbooks, and (c) e-modules make it easier for course students to complete exercises anywhere.